Pengaruh Solvabilitas Terhadap Price Book Value (PBV) - Clara Yully Diana Ekaristi; Apip Apip (ITB AAS INDONESIA, 2023)
Research on solvency and price book value is intended to determine the level of influence of Solvency on Price Book Value with the control variable liquidity, and profitability. The use of the purposive sampling method research method with certain criteria based on reports in the second, third, and fourth quarters of 2020 for food and beverage companies affected by the covid pandemic. The results of the multiple linear regression analysis show that there is a negative and significant DER effect on Price to Book Value, which projects that the higher the DER disclosure index, the negative and significant effect on the PBV of a company.